2021
DOI: 10.1038/s41598-021-96926-z
|View full text |Cite
|
Sign up to set email alerts
|

Determining the microbial and chemical contamination in Ecuador’s main rivers

Abstract: One major health issue is the microbial and chemical contamination of natural freshwater, particularly in Latin American countries, such as Ecuador, where it is still lacking wastewater treatment plants. This study analyzed the water quality in twelve rivers of Ecuador (Coastal, Andean, and Amazonian regions). All rivers showed levels of E. coli and total coliforms above the maximum limit according to International and Ecuadorian legislations. The most polluted rivers were Zamora, Esmeraldas and Machángara. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The relationship of Enterococcus faecium with faecal contamination can support the thesis that Ecuador rivers may be possible sources of this Gram-positive cocci, as recent research has reported that coliforms are above the maximal threshold established by USA, European and Brazilian guidelines ( Vinueza et al, 2021 ). Moreover, it is possible that other bacterial species, such as Rhodococcus ruber , which easily grows on plastic elastomers (usually polluting seawater and shores), participated in degrading pharmaceuticals available as ECs, for example diclofenac ( Mor and Sivan, 2008 ; Ivshina et al, 2019 ).…”
mentioning
confidence: 63%
“…The relationship of Enterococcus faecium with faecal contamination can support the thesis that Ecuador rivers may be possible sources of this Gram-positive cocci, as recent research has reported that coliforms are above the maximal threshold established by USA, European and Brazilian guidelines ( Vinueza et al, 2021 ). Moreover, it is possible that other bacterial species, such as Rhodococcus ruber , which easily grows on plastic elastomers (usually polluting seawater and shores), participated in degrading pharmaceuticals available as ECs, for example diclofenac ( Mor and Sivan, 2008 ; Ivshina et al, 2019 ).…”
mentioning
confidence: 63%
“…Coliforms were recorded in the Diyala River during the winter [24], at the Al-Azizziyah site in the Tigris River [26] and Tigris River near the water purification stations within Baghdad Province [23]. Coliforms were recorded in the Southern Gulf of Lake Tana [22], in Mariout lake in Egypt [37], Ecuador's main rivers due to untreated sewage, animal wastes and population activities [38].…”
Section: Fecal Coliform (Fc)mentioning
confidence: 99%
“…Domestic and industrial WW effluents are released through the public sewer system directly to freshwater bodies without any treatment ( Leon et al, 2020 ). The latter serve as primary sources of fresh water in rural areas for domestic activities such as personal hygiene, laundry, food preparation, and drinking ( SENAGUA, 2016 ; Vinueza et al, 2021 ). Consequently, there is a pressing need to shift the paradigm of wastewater management from one that is disposable to a model that is treatable, reusable, recyclable, and geared toward resource recovery ( Khan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%